Carmilla. 3, The eternal - Chu, Amy (Berger Books an imprint of Dark Horse, 2025)
"The final chapter of this Bram Stoker Award-winning graphic novel reimagination of Sheridan LeFanu's classic Carmilla! Athena's daughter Ella journeys to Oxford, England where a mysterious university benefactor hires her for what seems like a simple research position, but leads her straight into the heart of danger...and the Lo family back into the complicated web of Carmilla herself. As deaths begin to pile up on campus, Ella becomes entangled with a secret supernatural society of hard partying immortals. And just as Athena once did, Ella is about to discover some family secrets of her own... A seductive, supernatural thriller about mortality and mother/daughter relationships."--Publisher.